2014
DOI: 10.1159/000369586
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Treatment Resistance in Chronic Depression: A Pilot Study on Outcome and Feasibility of the Cognitive Behavioral Analysis System of Psychotherapy as an Inpatient Treatment Program

Abstract: Background: The Cognitive Behavioral Analysis System of Psychotherapy (CBASP), initially developed as an outpatient treatment for chronic depression (CD), has been adapted as a multidisciplinary 12-week inpatient program for CD. Methods: Seventy inpatients with CD and treatment resistance were included in a noncontrolled trial. The Hamilton Depression Rating Scale served as the primary outcome measure. Prospective naturalistic follow-up assessments were conducted 6 and 12 months after discharge. Results: Dropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
3
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 22 publications
8
55
3
7
Order By: Relevance
“…In addition, the initial phase of CBASP is frequently experienced as stressful by patients, since early trauma experiences are addressed and the common avoidance behavior is directly tackled. In line with this argument, a recent study [22] found over 65% of the patients experiencing a temporary worsening of symptoms mainly in the initial phase of CBASP. Temporary deterioration made remission (but not response) less likely by the end of therapy [22], suggesting extended treatment courses for this subgroup to reach remission as supported by other investigations [16,21,46,47].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In addition, the initial phase of CBASP is frequently experienced as stressful by patients, since early trauma experiences are addressed and the common avoidance behavior is directly tackled. In line with this argument, a recent study [22] found over 65% of the patients experiencing a temporary worsening of symptoms mainly in the initial phase of CBASP. Temporary deterioration made remission (but not response) less likely by the end of therapy [22], suggesting extended treatment courses for this subgroup to reach remission as supported by other investigations [16,21,46,47].…”
Section: Discussionmentioning
confidence: 62%
“…In the latter effectiveness trial [21], CBASP outperformed ‘care-as-usual' (consisting of medication and a mean of 23 psychotherapy sessions) after 52 weeks of treatment. Finally, in an open study, CBASP combined with medication also proved to be a feasible and promising treatment for therapy-resistant chronically depressed inpatients [22]. …”
Section: Introductionmentioning
confidence: 99%
“…CBASP specifically aims at the healing of traumatic interpersonal experiences, which may be the reason why it is particularly effective in patients who experienced childhood trauma [9] like our patient (especially emotional neglect and emotional abuse). Evidence for CBASP is encouraging [1,10] also in an inpatient setting for patients with severe treatment resistance [4]. The inpatient setting allows for a high frequency of healing interpersonal experiences, which may have been beneficial for the patient reported here.…”
Section: Discussionmentioning
confidence: 99%
“…After ECT, the patient participated in our inpatient CBASP program [4] comprising individual therapy (2 × 50 min/week), group psychotherapy (2 × 90 min/week), and nurse-patient encounters (at least 1 × 30 min/week). Significant-other history and transference hypotheses were compiled at the beginning, followed by frequent situational analyses with role playing in individual and group therapy sessions.…”
Section: Discussionmentioning
confidence: 99%
“…In our pilot study, two core techniques of CBASP, the Kiesler circle (interpersonal circumplex model) and situational analysis, were applied in 6 inpatient group therapy sessions for patients with comorbid substance use and depression. For a description of these interpersonal group strategies see Brakemeier et al [5]. Addressing interpersonal characteristics and problems in patients with comorbid substance use disorders and depression might be a successful strategy [6].…”
Section: Tablementioning
confidence: 99%